SARS-CoV-2 vaccine-associated-tinnitus: A review. (March 2022) - Ahmed, Syed Hassan; Waseem, Summaiyya; Shaikh, Taha Gul; Qadir, Nashwa Abdul; Siddiqui, Sarush Ahmed; Ullah, Irfan; Waris, Abdul; Yousaf, Zohaib
Abstract: The global vaccination drive against severe acute respiratory syndrome coronavirus-2 is being pursued at a historic pace. Unexpected adverse effects have been reported following vaccination, including thrombotic thrombocytopenia, myocarditis, amongst others. More recently, some cases of tinnitus are reported post-vaccination. According to the Vaccine Adverse Events Reporting System (VAERS), 12, 247 cases of coronavirus post-vaccination tinnitus have been reported till September 14, 2021. To the best of our knowledge, this is the first review evaluating any otologic manifestation following vaccine administration and aims to evaluate the potential pathophysiology, clinical approach, and treatment. Although the incidence is infrequent, there is a need to understand the precise mechanisms and treatment for vaccine-associated-tinnitus. Highlights: The COVID-19 global vaccination program has significantly reduced hospitalization and deaths due to infection. According to VAERS, 12, 247 cases of coronavirus post-vaccination tinnitus have been reported till September 14, 2021. This review highlights the potential mechanism, diagnosis and management of COVID-19 vaccine associated tinnitus. Corticosteroids were the first line treatment options for SARS-CoV-2 vaccine-associated tinnitus.